Shape-sensing Robotic-assisted Bronchoscopy (SS-RAB) in Sampling Peripheral Pulmonary Nodules: A Prospective, Multicenter Clinical Feasibility Study in China - Xie, Fangfang; Zhang, Quncheng; Mu, Chuanyong; Zhang, Qin; Yang, Huizhen; Mao, Jingyu; Simoff, Michael J; Huang, Jian'an; Zhang, Xiaoju; Sun, Jiayuan (Journal of bronchology & interventional pulmonology, 2024)
The ION system is a shape-sensing robotic-assisted bronchoscopy (SS-RAB) platform developed to biopsy peripheral pulmonary nodules (PPNs). There is a lack of data describing the use of this system in the Chinese population. The study aimed to assess the feasibility and safety of using SS-RAB to diagnose PPNs across multiple centers within China. This prospective, multicenter study used SS-RAB in consecutive patients with solid or sub-solid PPNs 8 to 30 mm in largest diameter. Primary endpoints were diagnostic yield and the rates of procedure- or device-related complications. Radial endobronchial ultrasound (rEBUS) was to confirm lesion localization, followed by sampling, using the Flexision biopsy needle, biopsy forceps, and cytology brush. Subjects with nonmalignant index biopsy results were followed up to 6 months. A total of 90 PPNs were biopsied from 90 subjects across 3 centers using SS-RAB. The median nodule size was 19.4 mm (IQR: 19.3, 24.6) in the largest dimension. In all (100%) cases, the catheter successfully reached the target nodule with tissue samples obtained. The diagnostic yield was 87.8% with a sensitivity for malignancy of 87.7% (71/81). In a univariate analysis, nodule lobar location, presence of bronchus sign, and rEBUS view were associated with a diagnostic sample, but only rEBUS view showed an association in a multivariate analysis. The overall pneumothorax rate was 1.1% without pneumothorax requiring intervention, and there was no periprocedural bleeding. As an emerging technology in the Chinese population, SS-RAB can safely biopsy PPNs with strong diagnostic performance.